2016
DOI: 10.1186/s12891-015-0848-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of trabecular bone microstructure in osteoporotic femoral heads in human patients: in vivo study using multidetector row computed tomography

Abstract: BackgroundLag screw position is very important in the treatment of intertrochanteric femoral fracture to prevent complications such as screw cut-out. Current studies recommend central or inferior placement of the lag screw on the anteroposterior radiograph, and central placement on the lateral radiographs. These reports are based on radiographic evaluation, but few studies have investigated the importance of bone quality at the site of lag screw placement. In this study, we used multidetector row computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In our clinical experience, there are two malpositions of the PFN which can cause pull-out of the nail but no delay or non-union in the fracture line. Munemoto et al ( 20 ) reported hip multidetector row CT in 10 elderly patients and found the highest bone microstructure quality, in the weight-bearing part, in the superior site of the femoral head. In the femoral neck the greatest bone quality was found in the inferior region.…”
Section: Discussionmentioning
confidence: 99%
“…In our clinical experience, there are two malpositions of the PFN which can cause pull-out of the nail but no delay or non-union in the fracture line. Munemoto et al ( 20 ) reported hip multidetector row CT in 10 elderly patients and found the highest bone microstructure quality, in the weight-bearing part, in the superior site of the femoral head. In the femoral neck the greatest bone quality was found in the inferior region.…”
Section: Discussionmentioning
confidence: 99%
“…The left ankle joints of the rats were fixed in 70% ethanol and scanned with a μ-CT system (TOSCANER-32300μFD, Toshiba, Tokyo, Japan). The reconstructed data sets were examined with three-dimensional data analysis software (TRI/3-D-BON, Ratoc System Engineering Co., Tokyo, Japan; n = 4 for each group) [35]. The regions of interest were defined in the whole talus bones.…”
Section: Methodsmentioning
confidence: 99%
“…However, the facet orientation in the lumbar region has been found irregular alteration in lumbar disc herniation patients [ 28 ]. Also, the facet forces have been found amplification under excessive physiological loads that could be induced by LBP [ 29 ].…”
Section: Introductionmentioning
confidence: 99%